2020
DOI: 10.1186/s40104-020-00503-9
|View full text |Cite
|
Sign up to set email alerts
|

Beef heifer fertility: importance of management practices and technological advancements

Abstract: The development of replacement heifers is at the core of cow-calf beef production systems. In 2020, the USDA, National Agricultural Statistics Service reported 5.771 million beef heifers, 500 pounds and over, are under development for cow replacement. A compilation of data from several studies indicate that between 85% and 95% of these heifers will become pregnant in their first breeding season. Several thousands of heifers being raised for replacement may not deliver a calf on their first breeding season and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 99 publications
1
28
0
Order By: Relevance
“…Conception rates in these four trials ranged between 80% and 100% regardless of vaccination group and are consistent with the 64% to 95% range expected for first breedingseason pregnancy rates in beef heifers [32]. Rates were similar between vaccinated and unvaccinated animals, with no significant differences noted between groups in any of the 4 studies reported here.…”
Section: Discussionsupporting
confidence: 83%
“…Conception rates in these four trials ranged between 80% and 100% regardless of vaccination group and are consistent with the 64% to 95% range expected for first breedingseason pregnancy rates in beef heifers [32]. Rates were similar between vaccinated and unvaccinated animals, with no significant differences noted between groups in any of the 4 studies reported here.…”
Section: Discussionsupporting
confidence: 83%
“…In this study, plasma BHBA levels were not influenced by a change in maternal energy density during the last 45 d before parturition. The reasons for the discrepancies in the effects of prepartum maternal energy density on BHBA concentrations between studies are not clear but include many factors, such as energy requirements, animal breed, age, and body condition 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Reproductive failure remains one of the most signi cant problems in the beef and dairy cattle industries despite advances in genetic selection, arti cial insemination, and improved feeding and management [3,34]. Emerging evidence derived from human and vertebrate animal models suggests that the microbiomes residing within the female and male urogenital tract are important for reproductive health and fertility.…”
Section: Discussionmentioning
confidence: 99%